Exploring the role of NLRP3 infalmmasome in diabetes: a literature review and bibliometric analysis - Tan, Yi; Chen, Shaotao; Gao, Tianjiao; Wang, Sixian; Zhou, Xinfeng; Liu, Mingjun (Frontiers in Endocrinology, 2024)
Background:Diabetes has emerged as the foremost public health challenge of the 21st century, with a notable shift towards managing it through an inflammatory lens. This study seeks to investigate the role of NLRP3 infalmmasome in diabetes over the past ten years, leveraging bibliometric analysis to pinpoint prevailing trends, underscore critical focal points, and establish a roadmap for subsequent research endeavors. Method: A literature search was conducted based on the SCI-E database, and all recorded results were downloaded in plain text format for subsequent analysis. The analysis was carried out using Vosviewer1.6.18, citespace6.3R1, and Microsoft Excel 2021 software, focusing on the following terms: country, institution, author, journal, references, and keywords. Results: From January 1, 2014, to December 31, 2023, a total of 1373 articles were retrieved, with China, the United States, and Italy contributing the majority of records. Harbin Medical University, Nanjing Medical University, and Central South University stand as the top three most productive institutions. "International Journal of Molecular Sciences" leads the way with the highest number of publications, closely followed by "Frontiers in Immunology" and "Frontiers in Pharmacology." Authors Wang Wei boast the most publications, closely followed by Li Xiang and Wang Yan. Within the superimposed keyword network, four primary clusters emerge: (1) exploring the link between NLRP3 infalmmasome and inflammatory diseases like diabetes; (2) investigating the cellular-level pathogenesis of diabetes-related conditions; (3) examining diabetes characteristics and associated suppression techniques; (4) studying cell morphology alterations, including pyroptosis. Over the past five years, key topics in this field have revolved around the "heart", "damage", "caspase 1 activation", "NLRP3", and "diabetic kidney disease". Conclusion: This paper has identified the hot spots and trends concerning the role of NLRP3 infalmmasome in diabetes, thereby providing a valuable reference for future research. Furthermore, it is anticipated that pyroptosis and diabetes-related diseases will become frontier research topics that may garner significant attention in the coming years.